A novel double-stranded RNA mycovirus isolated from Trichoderma harzianum - Liu, Chenchen; Li, Mei; Redda, Estifanos Tsegaye; Mei, Jie; Zhang, Jiantai; Wu, Beilei; Jiang, Xiliang (Virology journal, 2019)
Background Trichoderma spp. are used extensively in agriculture as biological control agents to prevent soil-borne plant diseases. In recent years, mycoviruses from fungi have attracted increasing attention due to their effects on their hosts, but Trichoderma mycoviruses have not been the subject of extensive study. We sought to discover novel mycoviruses from Trichoderma spp . and to determine the effects of the biocontrol function of Trichoderma spp. Methods Mycoviruses were screened by dsRNA extraction and metagenomic analysis. RT-PCR, 5′ RACE, and 3′ RACE were used to obtain the genome sequence. MEGA software was used to classify the new mycovirus. The effects of the identified mycovirus on the biological properties of the host strain 525 were evaluated using cucumber plants and Fusarium oxysporum f. sp. cucumerinum . Results A novel mycovirus, Trichoderma harzianum mycovirus 1 (ThMV1) (accession number MH155602), was discovered in Trichoderma harzianum strain 525, a soil-borne fungus collected from Inner Mongolia, China. The mycovirus exhibited a double-stranded RNA (dsRNA) genome with a complete genome sequence of 3160 base pairs and two open reading frames (ORFs) on the negative strand. Phylogenetic analysis indicated that it belongs to an unclassified family of dsRNA mycoviruses. The removal of ThMV1 from the host 525 strain reduced host biomass production and improved the biocontrol capability of the host for Fusarium oxysporum f. sp. cucumerinum . At same time, the presence of ThMV1 improved the growth of cucumber. Conclusion ThMV1 is a new unclassified mycovirus found in T. harzianum . It not only affects the phenotype of the host strain but also reduces its biocontrol function, which sheds light on the interaction between the mycovirus and Trichoderma spp.